Sufi Moral Teachings in Habiburrahman El-Shirazy's Ayat-Ayat Cinta: Relevance of Classical Ethics in the Age of Globalization - Ade Susana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article examines the Sufi moral teachings embedded in Habiburrahman El Shirazy’s novel Ayat-Ayat Cinta and their relevance to the challenges of ethical and spiritual life in the contemporary age of globalization. As global culture increasingly promotes materialism, individualism, and moral relativism, classical Sufi ethics—rooted in the cultivation of akhlaq al-karimah (noble character)—offer an alternative framework for restoring balance and spiritual depth in human life. This study employs a qualitative library research method with a descriptive-analytical approach, drawing upon primary data from the novel and secondary sources from classical Sufi scholars, especially Imam al-Ghazali. The findings reveal that El Shirazy integrates central Sufi virtues such as faqr (detachment from worldly attachments), sabr (patience in adversity), and tawakkul (trust in divine providence) into the narrative, particularly through the main character’s responses to personal and moral dilemmas. These values, while rooted in classical Islamic ethics, are presented in a way that resonates with modern readers, demonstrating the continued relevance of Sufi moral teachings in addressing ethical crises in the global era. Thus, Ayat-Ayat Cinta not only serves as popular Islamic fiction but also as a medium of da‘wah that recontextualizes timeless spiritual values for contemporary society.